1 Answer | Add Yours
You should come up with the substitution `alpha = angle ` and `3.14 = pi` .
You need to expand the cosine using the formula `cos(x-y) = cosx*cosy + sin x*sin y` such that:
`cos(pi - alpha) = cos pi*cos alpha + sin pi*sin alpha`
Using `cos pi = -1` and `sin pi = 0` yields:
`cos(pi - alpha) = -cos alpha + 0*sin alpha`
`cos(pi - alpha) = -cos alpha`
Hence, evaluating `cos(pi - alpha)` yields the negative value of cos alpha such that: `cos(pi - alpha) = -cos alpha` .
We’ve answered 319,199 questions. We can answer yours, too.Ask a question